IMPROVING THE RESULT OF LEARNING ENGLISH BY USING PROBLEM SOLVING APPROACH - Fatimah Sari Siregar (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: This research begins with the problem of learning English in class VII of SMP Negeri 2 Padangsidimpuan where most students are less interested in learning and have difficulty understanding English learning materials, so the learning outcomes obtained by students are low. Therefore, to improve student learning outcomes in English language learning a Problem Solving Approach is applied to VII grade students of SMP Negeri 2 Padangsidimpuan. This research is a classroom action research using a qualitative approach. This research was carried out at SMP Negeri 2 Padangsidimpuan with research subjects of Grade VII students totaling 20 students. The instruments used to collect data were in the form of observation sheets, documentation and test results of learning. Data obtained in the study were analyzed using qualitative and quantitative data analysis. this is done in two cycles and each cycle consists of one meeting. Based on the results of research in learning English using the Problem Solving Approach seen an increase in student learning outcomes. From the analysis of student learning outcomes showed a significant improvement, where from the results of the end of the first cycle test, the average value obtained by students reached 6.4 with completeness of 60%. While in the second cycle has increased, where the average class reached 8.2 with a classical completeness of 85%. Thus it can be concluded that the use of the Problem Solving Approach can improve English learning outcomes of Grade VII students of SMP Negeri 2 Padangsidimpuan. Keywords: Learning English; Approach Problem Solving, method; Classroom Action Reseacrh